Combination of Hypertrophic Pachymeningitis, PR3-ANCA-positive Vasculitis, and Relapsing Polychondritis (2011)
Relapsing polychondritis (RP) is a rare connective tissue disease characterized by inflammation and destruction of cartilaginous tissue1. Although the exact underlying pathologic mechanism is unknown, it is widely accepted that there is a role of an autoimmune response in most cases2. Patients may have lung, renal, ocular, joint, and vascular compromise. Central nervous system (CNS) involvement is rare, and few cases have been described. We describe 3 patients with RP and CNS involvement manifested as hypertrophic pachymeningitis (HP), an inflammatory process that thickens the dura mater.